High Performance Perovskite Photodiodes via Molecule‐Assisted Interfacial and Bulk Modulations - Yan, Yuting; Zhou, Bin; Lin, Xi; Shi, Jian; Wang, Shasha; Qu, Duo; Tu, Yongguang; Luo, Xiaoguang; Huang, Wei (Small (Weinheim an der Bergstrasse, Germany), 2025)
Metal halide perovskites have attracted significant attention in photodetection due to their superior photophysical properties and improved stability. However, the performance of their photodiodes is predominantly limited by non‐radiative recombination within the perovskite layer or at interfaces. Here, molecular engineering via phenylethylammonium chloride for interfacial modulation and methylenediammonium dichloride for bulk modulation is introduced into vertical perovskite photodiodes to boost the photodetection performance. The responsivity at 635 nm excitation increased from 0.09 to 0.33 A W−1 with interfacial modulation, compared to the original perovskite device, and is further improved to 0.40 A W−1 with the combined effects of interfacial and bulk modulations (i.e., synergistic bimolecular engineering). The optimized photodiodes demonstrated high detectivity of over 1011 Jones, a rapid response time of ≈1 µs, and a linear dynamic range of ≈100 dB. Furthermore, the photocurrent exhibited a U‐shaped dependence on temperature ranging from 10 to 300 K, with linearity breaking under strong illumination at low temperatures. These results confirmed that molecular engineering is the promising strategy for achieving high‐performance perovskite photodetectors. Through molecular engineering of interfacial and bulk modulations, the photoresponse of metal halide perovskite photodiodes has been significantly enhanced. The responsivity reaches 0.40 A W−1, with a detectivity exceeding 10¹¹ Jones, and a rapid response time of ≈1 µs. Additionally, the photocurrent displays a U‐shaped temperature dependence over the range of 10 to 300 K.